Quantitative linkage between the stress at dislocation channel – Grain boundary interaction sites and irradiation assisted stress corrosion crack initiation. (15th May 2019) - Johnson, D.C.; Kuhr, B.; Farkas, D.; Was, G.S.
Abstract: Localized deformation has emerged as a key factor in the crack initiation process for irradiated steels, as cracks are observed to nucleate preferentially at these sites. Using high resolution electron backscatter diffraction (HREBSD), the local stress tensor surrounding the dislocation channel-grain boundary interaction sites was quantified and coupled with fully determined grain boundary plane orientation information to determine, for the first time, the relationship between grain boundary normal stress and intergranular crack initiation in irradiated austenitic stainless steel. A Fe13Cr15Ni alloy was strained in simulated boiling water reactor, normal water chemistry after quantifying the residual stress tensor at discontinuous dislocation channel – grain boundary interaction sites where grain boundaries were determined to be well oriented with respect to the loading axis. Local stresses at the grain boundary were observed to reach magnitudes greater than 1.5 GPa at a distance of 200 nm from the intersection between the dislocation channel and the grain boundary. A pseudo-threshold stress of 0.9 GPa was measured, below which no cracking was observed. As the stress acting normal to the grain boundary increased above this value, the susceptibility to cracking increased with the cracking fraction reaching 100% at the high end of the stress range. This study shows for the first time that not only does intersection between discontinuous dislocation channels and grain boundaries result in peak local stresses, but the magnitude of the local tensile stress drives the crack initiation process. Graphical abstract: Image 1